Development of agroclimatic zoning model to delimit the potential growing areas for macaw palm (Acrocomia aculeata) - Falasca, Silvia Viviana; Ulberich, Ana Cristina; Pitta Alvarez, Sandra (Springer, 2018)
The growing biodiesel production requires the use of new technologies and alternative feedstocks to maintain the growing demand of this biofuel. The macaw (Acrocomia aculeata) is a palm native to Argentina whose fruits present high oil content. Due to its tolerance to prolonged drought, it is a promising crop for biodiesel and biokerosene production. The aim of this work was to design an agroclimatic zoning model to define the potential growing areas from macaw in Argentina. To define the agroclimatic suitability to produce oil, it was necessary to identify the requirements, limits, and biometeorological tolerance for this palm. In order to define the agroclimatic fitness of this crop in Argentina, the meteorological data corresponding to the period 1981–2010 were employed. The agroclimatic indices were integrated in a Geographic Information System. The maps were superimposed and the overlapping regions delineated the agroclimatic zoning. The agroclimatic zonation classified zones with homogeneous characteristics responding to bioclimatic requirements of this species, resulting in optimal, very suitable, suitable, and nonsuitable areas for macaw cultivation. The authors designed an agroclimatic zoning model based on bibliography. This model can be used in any part of the world, employing the same agroclimatic indices presented in this work.